Advances in the Use of Graphene Nanocomposites for the Electrochemical Determination of Glucose: A Review - Zhou, Qinwei; Fan, Boyuan; Zhu, Jiangwei; Fu, Liqing; Wu, Weihong (Current Pharmaceutical Analysis, 2022)
Background: Glucose detection is of great significance in biomedicine. In clinical medicine, diabetes seriously endangers human health. By accurately measuring the blood glucose content of diabetic patients, diabetes can be effectively monitored and treated. At present, there are many methods for measuring glucose content, such as chromatography, spectroscopy, and electrochemical methods. Among them, electrochemical glucose sensors are widely used because of their high reliability, low cost, and easy operation. Methods: Combining graphene with other nanomaterials (including graphene, metal oxides, semiconductor nanoparticles, polymers, dye molecules, ionic liquids and biomolecules) is an effective way to expand or enhance the sensing performance. Results: The composite of graphene and nanomaterials is an effective way to enhance the functionality of the electrochemical sensor. Graphene can accelerate electron transfer and realize direct electrochemistry and biological sensing. At the same time, graphene derivatives with rich composition and structure provide the possibility to further regulate their electrochemical performance. These graphene composite-based biosensors have shown excellent sensitivity and selectivity for glucose detection. Conclusion: Electrochemical glucose sensors based on graphene composite have received extensive attention. Although these materials have made significant progress in improving the sensitivity, lowering the detection limit and broadening the linear range, there are still facing challenges that require further study.
Keywords: glucose